In-air versus underwater comparison of 3D reconstruction accuracy using action sport cameras. (25th January 2017) - Bernardina, Gustavo R.D.; Cerveri, Pietro; Barros, Ricardo M.L.; Marins, João C.B.; Silvatti, Amanda P.
Abstract: Action sport cameras (ASC) have achieved a large consensus for recreational purposes due to ongoing cost decrease, image resolution and frame rate increase, along with plug-and-play usability. Consequently, they have been recently considered for sport gesture studies and quantitative athletic performance evaluation. In this paper, we evaluated the potential of two ASCs (GoPro Hero3+) for in-air (laboratory) and underwater (swimming pool) three-dimensional (3D) motion analysis as a function of different camera setups involving the acquisition frequency, image resolution and field of view. This is motivated by the fact that in swimming, movement cycles are characterized by underwater and in-air phases what imposes the technical challenge of having a split volume configuration: an underwater measurement volume observed by underwater cameras and an in-air measurement volume observed by in-air cameras. The reconstruction of whole swimming cycles requires thus merging of simultaneous measurements acquired in both volumes. Characterizing and optimizing the instrumental errors of such a configuration makes mandatory the assessment of the instrumental errors of both volumes. In order to calibrate the camera stereo pair, black spherical markers placed on two calibration tools, used both in-air and underwater, and a two-step nonlinear optimization were exploited. The 3D reconstruction accuracy of testing markers and the repeatability of the estimated camera parameters accounted for system performance. For both environments, statistical tests were focused on the comparison of the different camera configurations. Then, each camera configuration was compared across the two environments. In all assessed resolutions, and in both environments, the reconstruction error (true distance between the two testing markers) was less than 3mm and the error related to the working volume diagonal was in the range of 1:2000 (3×1.3×1.5 m 3 ) to 1:7000 (4.5×2.2×1.5 m 3 ) in agreement with the literature. Statistically, the 3D accuracy obtained in the in-air environment was poorer ( p <10 −5 ) than the one in the underwater environment, across all the tested camera configurations. Related to the repeatability of the camera parameters, we found a very low variability in both environments (1.7% and 2.9%, in-air and underwater). This result encourage the use of ASC technology to perform quantitative reconstruction both in-air and underwater environments.